2020
DOI: 10.3390/ani10050772
|View full text |Cite
|
Sign up to set email alerts
|

Expectations Versus Reality: Long-Term Research on the Dog–Owner Relationship

Abstract: In the framework of the early prevention of problems in the owner–dog relationship, it is important to have a broad perspective on the development of this relationship over time, starting before people actually acquire a dog. People who currently (or previously) own(ed) a dog can rely on their experiences when considering a new dog, while this knowledge is unavailable to first time dog-owners. In this study, we explore how self-efficacy, social comparison, perceptions about the (dis)advantages of ownership and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…Conclusive results were obtained regarding the feeling generated from their interactions with their pet(s) and the benefits they provided to the participants’ well-being from a biopsychosocial perspective, which is in line with previous research [ 58 , 84 ]. Additionally, the applied models showed that living with an animal provided important benefits for the humans, in agreement with the evidence found in recent research [ 28 , 85 , 86 , 87 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Conclusive results were obtained regarding the feeling generated from their interactions with their pet(s) and the benefits they provided to the participants’ well-being from a biopsychosocial perspective, which is in line with previous research [ 58 , 84 ]. Additionally, the applied models showed that living with an animal provided important benefits for the humans, in agreement with the evidence found in recent research [ 28 , 85 , 86 , 87 ].…”
Section: Discussionsupporting
confidence: 90%
“…The sociodemographic variable of sex was only shown to be predictive regarding happiness, where a woman had twice as much chance of developing happiness because of interacting with a pet than a man, which is in line with other studies [ 87 , 92 ], where women showed higher scores than men regarding emotional aspects [ 93 ]. The other sociodemographic variable par excellence, namely, age, was not found to be significant in any of the logistic regression models.…”
Section: Discussionsupporting
confidence: 89%
“…Researchers suggest owner expectations to have a significant influence on the owner-dog relationship [ 34 , 47 , 48 ]. Owners often have expectations prior to acquiring a dog, but these expectations are not always accurate [ 65 ]. Prospective owners, especially those that have never previously owned a dog, may greatly benefit from educational efforts designed to provide a more realistic expectation of the potential challenges and behaviours they may encounter.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be meaningful to explore owner expectations and their effect on the owner-dog relationship as the current study did not allow for a thorough investigation. Owner expectations are not always accurate, and the owner-dog relationship may be heavily influenced as a result [ 46 48 , 65 ]. Finally, investigation of the motives of owners that chose to acquire dogs from non-Canadian sources may reveal interesting sociopolitical factors influencing dog importation.…”
Section: Discussionmentioning
confidence: 99%
“…Weiss et al [55] reported that 27.3% of participants stated appearance was the single most important reason for choosing a dog, however after a few months of ownership the value of appearance dramatically reduces and behaviour and temperament are seen as much more important [18]. New owners often have to adjust their perception of dog ownership within the first few months of ownership [56] and a major theme amongst relinquishing dog owners is that they would devote more time, thought and planning to considering getting another dog in the future [57]. Care should be taken on providing advice for previous or current dog owners who consistently have greater odds of expecting benefits and reduced odds of expecting challenges with a new dog [58] and who may consider themselves experienced enough not to need to research further [52].…”
Section: Behaviour Problemsmentioning
confidence: 99%